Analysis of the Performance of the West Nusa Tenggara Provincial Industry Office in Increasing the Added Value of Food Small and Medium Industry Products (SMIs) in Mataram City - Al Isnaini, Muh. Faizul; Jumaidi, Lalu Takdir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the performance of the West Nusa Tenggara Provincial (NTB) Industry Office in increasing the added value of Food Small and Medium Industries (SMEs) products in Mataram City. The research method used is qualitative with a case study approach. The data collection techniques in this study are through observation, interviews and documentation. The informants in this study are parties from the Department of Industry and Food SMEs in Mataram City. The results of the study show that the performance of the NTB Provincial Industry Office in increasing the added value of Food SME products in Mataram City is considered quite good even though it still needs improvement and development in several aspects. The NTB Provincial Industry Office needs to continue to innovate in providing more comprehensive support, including in the aspects of capital, marketing, and raw material processing. In addition, the NTB Provincial Industry Office also increases the added value of food SMEs products in Mataram City based on four inicators, namely work quality indicators, quantity indicators, timeliness indicators, and effectiveness indicators.